Green actions for innovative cities. The new agri-food landscape - Emanuele Sommariva; Nicola Valentino Canessa; Giorgia Tucci (Agathón)
The role of ecosystem services is interlinked with the growing awareness of research and development funding programmes sensitive to green infrastructure and urban greening strategies. They become one of the structural components for the ecological transition of European urban agendas, in line with the Sustainable Development Goals of Agenda 2030. Ecosystem services are a new parameter for the assessment of urban green infrastructure and re-naturalisation processes, which also aim to counteract the effects of climate change (i.e., flooding, heat islands), or to promote the conservation, resilience and biodiversity of natural habitats. Specifically, urban agriculture and community gardens play an important role, helping to secure various socio-ecological benefits on a local basis and to promote access to healthy, Zero Km sources. In order to encourage good practices within the contemporary agro-urban scenario, the contribution outlines novel ideas on circularity and recycling of waste from across the food chain from the European project Creative Food Cycles.